Parents and childhood functional abdominal pain : a narrative review of the literature - Tilburg, Miranda A. L. van (Array, 2018)
Functional Abdominal Pain Disorders (FAPD) tend to run in families and recent research has suggested that parents play an important role in managing child's pain. The aim of this narrative review is to examine the role of parents in child FAPD. Most research has applied social learning theory, where the child learns how to deal with pain from their parents through either modeling or reinforcement. Parental reinforcement of inappropriate illness behaviors, such as excusing a child from activities, increases pain severity as well as pain disability. A parent may reinforce illness behaviors in order to protect their child as the pain is perceived as a high threat. These parents also tend to catastrophize about their child's pain. Interventions focused on altering parental modeling, protective behaviors, pain threat and catastrophizing have been shown to help improve child pain outcomes. These findings emphasize the importance of intervening on a family level for childhood FAPD disorders.